Light Emitting Diode (LED) Fluorescent Microscopy: a Milestone in the Detection of Paucibacillary Mycobacterium in Case of Pulmonary Tuberculosis (Bangladesh Medical Journal, 2012)
In Bangladesh with a large number of pulmonary tuberculosis cases and financial constraints with high HIV risk, evaluation of scanty i.e paucibacillary cases has great importance. To study the efficacy of Light Emitting Diode fluorescent microscopy in the diagnosis of pulmonary tuberculosis specially paucibacillary cases in comparison to conventional fluorescent microscopy, Ziehl-Neelsen staining and culture of sputum samples from patients suspected of pulmonary tuberculosis. 150 sputum samples collected from the patients suspected of pulmonary tuberculosis were processed by the Petroff's method, and subjected to Ziehl-Neelsen staining (ZN), which were examined by both LED and conventional fluorescent microscope (CFM) and culture on Lowenstein- Jensen media (gold standard) for detection of Mycobacterium tuberculosis. In this study, out of 150 patients 14.67%, 8.67%, 4% cases were detected as paucibacillary (Scanty) cases by LED, CFM, ZN respectively. LED fluorescent microscopy is more effective in the detection of paucibacillary cases of pulmonary tuberculosis than other methods of microscopic examination. DOI: http://dx.doi.org/10.3329/bmj.v40i1.9958 BMJ 2011; 40(1): 22-26